Measuring supernatural belief implicitly using the Affect Misattribution Procedure. Issue 4 (1st October 2020) - Ross, Robert M.; Brown-Iannuzzi, Jazmin L.; Gervais, Will M.; Jong, Jonathan; Lanman, Jonathan A.; McKay, Ryan; Pennycook, Gordon
ABSTRACT: Asking about religious beliefs, or lack thereof, is a sensitive and complex issue. Due to cultural norms, people may be motivated to respond in a socially desirable way. In addition, deliberating about beliefs may yield different responses than intuition-based responses. To develop a better understanding of the relationship between intuition and self-reported belief, we developed a new implicit measure of supernatural belief. Specifically, we adapted the Affective Misattribution Procedure (AMP) to measure supernatural belief. In a preregistered online study of 404 American participants, we found that the strength of associations between supernatural entities (e.g., god, devil, heaven ) and the concept "real" (as opposed to the concept "imaginary") predicted self-reported supernatural belief and self-reported religious behavior, and these associations were of comparable magnitude to those found in studies where supernatural belief was measured implicitly using the Implicit Association Test (IAT). These results provide provisional evidence that the AMP can be used as an implicit measure of supernatural belief.